Evaluation of the Merdeka Curriculum in Educational Institutions: A Systematic Literature Review of Strategies, Challenges, and Student Learning Outcomes - Mujiburrahman, Mujiburrahman; Ratnaya, I Gede; Parwata, I Gusti Lanang Agung; Budhyani, I Dewa Ayu Made (Jurnal Paedagogy, 2025)
This study aims to evaluate the implementation of the Merdeka Curriculum across various educational institutions in Indonesia through a Systematic Literature Review (SLR) supported by bibliometric analysis. A total of 30 Scopus-indexed articles, were analyzed using the PRISMA protocol to identify implementation strategies, key challenges, and student learning outcomes following the curriculum adoption. The findings indicate that common implementation strategies include teacher professional development, school leadership enhancement, project-based learning, and the integration of local values into the curriculum. Nevertheless, several challenges remain, such as limited pedagogical competencies, inadequate digital infrastructure, and disparities in curriculum quality across regions. In terms of learning outcomes, the Merdeka Curriculum has shown potential in enhancing student engagement, critical thinking, and independent learning, particularly in institutions with strong institutional readiness. The study recommends policies to improve teacher capacity, reduce administrative burdens, ensure equitable access to technology, and promote cross-sector collaboration as critical measures to strengthen curriculum implementation. This review contributes valuable insights for policymakers and educational practitioners in designing evidence-based strategies to support the success of Indonesia’s national curriculum reform.